In‑work poverty dynamics : trigger events and short‑term trajectories in Argentina - Poy Piñeiro, Santiago (2023)
Fil: Poy Piñeiro, Santiago. Pontificia Universidad Católica Argentina. Facultad de Ciencias Sociales. Observatorio de la Deuda Social Argentina; Argentina